2010
DOI: 10.1039/c0nr00426j
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of fullerene fusion and ejection in carbon nanotubes

Abstract: We present in situ experimental observations of fullerenes seamlessly fusing to single-walled carbon nanotubes. The morphing-entry of a fullerene to the interior of a nanotube is also captured. The confined (1D) motion of the newly-encapsulated fullerene within its host attests to the actual change from the exterior to interior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…When applying an electrical current through the CNTs, the motion of particles inside is very complicated and extensive studies have shown that electromigration, thermomigration, and evaporation can take place at the same time . The electron‐beam irradiation effects can induce coalescence of fullerenes inside CNTs, or coalescence between a fullerene residing on the outside wall of a CNT and the CNT ( Figure ), or even coalescence of two CNTs assisted by electric bias . When a graphene nanoribbon is encapulated in a CNT, the helical structure can merge into a CNT structure under electron‐beam irradiation …”
Section: In‐situ Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When applying an electrical current through the CNTs, the motion of particles inside is very complicated and extensive studies have shown that electromigration, thermomigration, and evaporation can take place at the same time . The electron‐beam irradiation effects can induce coalescence of fullerenes inside CNTs, or coalescence between a fullerene residing on the outside wall of a CNT and the CNT ( Figure ), or even coalescence of two CNTs assisted by electric bias . When a graphene nanoribbon is encapulated in a CNT, the helical structure can merge into a CNT structure under electron‐beam irradiation …”
Section: In‐situ Investigationsmentioning
confidence: 99%
“…In‐situ HRTEM observations of a fullerene ejection from the host single‐walled CNT, through penetration and necking‐off of a hump. Reprinted with permission . Copyright 2010, Royal Society of Chemistry.…”
Section: In‐situ Investigationsmentioning
confidence: 99%
“…Also, fullerenes fused onto CNT appeared to be unstable and it is still not clear under which condition a hump structure will form. In the previously reported hump structure, 23 well-separated fullerenes were nally observed in each case, which indicates a more stable fullerene structure. According to our in situ data, isolated fullerenes were found aer even $2 h of e-beam irradiation (see Fig.…”
Section: Experiments Results and Discussionmentioning
confidence: 48%
“…It is also worth noting that the observed fullerene structure is different from the previously reported hump structure (or a fused fullerene). 23 First, the hump structure shows no carbon wall distance of 0.33 nm (the graphite VdW layer distance), which is different from the situation of the encapsulated fullerene. The latter case should show a carbon wall distance of no less than 0.33 nm, which is in accordance with our results.…”
Section: Experiments Results and Discussionmentioning
confidence: 92%
“…Out of this numerous studies began to look at the combination, interactions, and transformations of different sp 2 carbon nanostructures. For example, fullerenes encapsulated inside carbon nanotubes, so-called peapods, generated great interest in their ability to form double-walled carbon nanotubes as well as other exotic behaviors. Fullerenes merging onto the outside of single walled carbon nanotubes and their morphing entry into a nanotube has been demonstrated . Graphite intercalated with fullerenes have also been examined in TEM …”
Section: Resultsmentioning
confidence: 99%